A Study on Performing Arts Education in Basic School Cultural Festivals in Ghana - Adjepong, Benjamin; Asiamah, Yaw Owusu (New Ideas Concerning Arts and Social Studies Vol. 1, 2025)
In the days gone by, the Ghanaian child acquired knowledge, skills and understanding in the performing arts through direct involvement and participation in the culture in which he or she belongs. This learning process has been interrupted primarily due to economic and social changes taking place in most African communities. The school has now become the main social institution which provides such learning experiences to children in society. Notwithstanding, it is not fulfilling this task effectively. An innovation which has been employed to equip Ghanaian children with knowledge, understanding and skills of their traditional performing arts practices is the introduction of the school cultural festivals by the Ghana Ministry of Education through the Ghana Education Service The disciplines of this festival include choral music performance, traditional music and drama performance, folk poetry recital, traditional drum language, and story-telling. This festival is organised annually and participants include basic and secondary school students. This paper, therefore, re-emphasises the role of the annual school cultural festivals in exposing Ghanaian basic school students at first-hand, to the processes of their traditional music, dance and drama practices.